IDENTIFIKASI JENIS DAN KERUSAKAN TUMBUHAN MANGROVE DI WILAYAH PESISIR PANTAI DESA TIAL KECAMATAN SALAHUTU - Renwarin, Nur Muhammad; Irwanto, Irwanto; Talaohu, Moda (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The village of Tial, located in the Salahutu Subdistrict, has a mangrove forest that plays an important role in protecting the coast from erosion. However, many people are unaware of the species of mangroves and the extent of the damage occurring. This study aims to determine the structure of the mangrove forest community, the level of damage, and the factors causing the damage. The methods used were quantitative descriptive methods in the form of surveys and observations, with the sampling technique being the Census method. The main data variables needed include the measurement of diversity index parameters and important value index (IVI) parameters, which include: density, relative density, frequency, relative frequency, dominance, and relative dominance. The results of this study indicate that the community types found on the coast of Tial Village are Sonneratia alba, Aegiceras floridum, Rhizophora mucronata, and Lumnitzera racemosa. The level of damage to the mangrove forest falls into the category of damaged (sparse), with a density level of <1000 trees/ha, specifically seedlings at 112/ha, saplings at 455/ha, and trees at 178/ha, and it has a diversity index H'<1, specifically seedlings at 0.63, saplings at 0.74, and trees at 1.16. The factors causing the damage to the mangrove forest on the coast of Tial Village include a lack of nutrient elements, lichen fungi, waste, abrasion and light intensity.